Sociopragmatics of Code Switching and Code Mixing in Reconciliation Case Proceedings: Shariah Courts of Northern Nigeria - Mohammed Ahmad Ado; Siti Jamilah Bidin (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
Due to the peculiarity of the spoken language identified among parties involved in Reconciliation Case Proceedings (RCP) and their arbitrators in the Shariah Reconciliation courts, this paper explores some sociopragmatic aspects of the Hausa natives (Northern Nigeria, West Africa) Shariah reconciliation Courts judicial discourse. To this end, 12 various case proceedings of family disputes on marital issues were recorded through audiovisual recordings. The data were coded and analysed using Nvivo 10, focusing, amongst others, on Searle’s taxonomy of speech acts of expressiveness. It was found that Code Switching and Code Mixings (CSCM) appeared/employed constantly by almost all classes of speakers during RCP. The findings revealed that it is a sociopragmatic culture, behaviour and attribute of Hausa speakers of using Hausa switched, lexical mixed of Hausa-English or Hausa-Arabic CSCM expressive utterances in RCP. Arabic Terminologies and Hausanised of Arabic lexical are also employed by speakers in order to affirm, assert reciprocity, show respect, express gratitude or intention, offer defence, minimise imposition, and seek confirmation or explanation as well as Generic or honorific names/titles in RCP. Finally, the paper demonstrates that it is a cultural practice that during RCP, Hausa language is dominantly used as a medium of communication, hence, sometimes due to the Arabic and Islamic cultural influence of Hausa natives as well as being English as an official language in the Nigerian settings, CSCM of both the three languages is found to be part of the common feature of RCP within Bauchi state Shariah Commission of Nigeria.